2008
DOI: 10.1099/mic.0.2008/017780-0
|View full text |Cite
|
Sign up to set email alerts
|

The new group of non-pathogenic plant-associated nitrogen-fixing Burkholderia spp. shares a conserved quorum-sensing system, which is tightly regulated by the RsaL repressor

Abstract: The new group of non-pathogenic plant-associated nitrogen-fixing Burkholderia spp. shares a conserved quorum-sensing system, which is tightly regulated by the RsaL repressor A novel group of nitrogen-fixing plant-associated Burkholderia species has emerged in the last few years. The purpose of this investigation was to determine if these species possess an Nacylhomoserine lactone (AHL) quorum-sensing (QS) cell-cell signalling system, and whether it is important for nitrogen fixation and other phenotypic featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
35
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 61 publications
(49 reference statements)
0
35
0
3
Order By: Relevance
“…In a previous study we reported the presence of an AHL-based QS system in the rice endophyte B. kururiensis designated BraI/R KUR , which produces and responds to 3-oxo-C 12 -HSL. It was determined that the BraI/R KUR system is stringently regulated by RsaL, and it is not involved in the regulation of nitrogen fixation or in other several important phenotypes (73). Importantly, BraI/R was found to be highly conserved in 20 species of the recently described cluster (73).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…In a previous study we reported the presence of an AHL-based QS system in the rice endophyte B. kururiensis designated BraI/R KUR , which produces and responds to 3-oxo-C 12 -HSL. It was determined that the BraI/R KUR system is stringently regulated by RsaL, and it is not involved in the regulation of nitrogen fixation or in other several important phenotypes (73). Importantly, BraI/R was found to be highly conserved in 20 species of the recently described cluster (73).…”
mentioning
confidence: 97%
“…The method used to detect siderophores was adapted from the universal chemical assay on chrome azurol S (CAS) agar plates (66,73). The cultures were harvested, and the pellets washed and adjusted to an OD 600 of 1.…”
mentioning
confidence: 99%
“…Foi comprovado que a B. kururiensis possui o sistema HSL de quorum sensing, chamado de BraI/R, que produz e responde ao 3-oxo-C 12 -HSL e é extremamente similar ao LasI/R de P. aeruginosa (nesta é interconectado com outros sistemas regulatórios e é o regulador global envolvido na regulação de muitos genes que possuem importância na virulência e colonização). 100 Também foi relatada a existência de uma outra molécula produzida por P. aeruginosa que possui efeito antibiofilmes, o ácido graxo insaturado cis-2-decenóico, porém, seu mecanismo de ação ainda não foi elucidado. 101 Desta forma a ação dos ramnolipídios pode ser otimizada pela presença destes compostos, ajudando a inibir a formação dos biofilmes.…”
Section: Propriedades Antibiofilmes Dos Biossurfactantesunclassified
“…AHLs are synthesized by synthase proteins and are detected by transcriptional regulators, which regulate the expression of many different target genes. The presence of well conserved QS systems have been described within Bcc species, where the system is composed of the synthase CepI and the regulator CepR (Lewenza et al, 1999); and in plant associated Burkholderia, which have a system based on the synthase BraI and the regulator BraR (Lewenza et al, 1999;Suarez-Moreno et al, 2008). These two conserved systems are not homologous and were found to be based on different AHL molecules: CepI/R system secretes and responds to C6-HSL and C8-HSL; and the BraI/R system to 3-oxo-C12-HSL and 3-oxo-C14-HSL depending in the strain (Lewenza et al, 1999;SuarezMoreno et al, 2008).…”
Section: Regulation At Transcriptional Levelmentioning
confidence: 99%